Shared parenting as an interpretation of the best interests of the child in custody disputes: what Malaysia learn from Australian experience - Che Soh @ Yusoff, Roslina (2010)
In most western countries there is now a consensus that shared parenting is the best alternative for children when their parents separate or divorce. Maintaining a relationship with both parents after divorce, by way of a shared parenting arrangement is said to be the best alternative to merely providing for contact among children and non-resident parents by way of a sole custody arrangement. Such an arrangement would minimise conflict between warring parents and maintain a healthy level of adjustment for the children, therefore diminishing the detrimental effects of parental conflict on children. The best interest of the child would be preserved as the child is able to retain a strong connection with both parents despite of parental break-up. The basis of this concept can be found in the United Nation Convention on Right of Child 1989, which clearly emphasized on the importance of both parents to be equally responsible for the upbringing of their children. This paper seeks to examine the extent of the laws and the judicial decisions in Malaysia in upholding shared parenting as the best interest of the child in custody disputes after parental divorce. In doing so, it attempts to provide an overview of the current law and the approach of the courts in granting custody orders. The paper will also highlight the problems of implementing shared parenting arrangement, particularly in cases involving determination of the religion of the child and domestic violence. As a comparison, it also seeks to examine the Australian legislation on custody disputes which has undergone a tremendous shift from sole custody standard to shared parental responsibility. The purpose is to learn from the Australian experience in advocating shared parenting as the primary custody standard for the best interest of the child in custody disputes and whether Malaysia may adopt a similar legislative amendment.